MILKU AL-YAMĪN: Diskursus dalam Al-Qur’an antara Teks dan Konteks - Hendri; Arsal (AL ITQAN: Jurnal Studi Al-Qur'an, 2025)
The relationship between the text and its context in the term Milku Al-Yamīn is often understood differences and shifts in meaning from classical to contemporary times, which are inseparable from social factors and thus influence as a form of ownership of slaves or prisoners of war in pre-Islamic Arab society. However, this interpretation often causes debate when confronted with modern human values. This study uses a qualitative approach with a literature study and thematic interpretation (maudhū‘i) method, combined with socio-historical analysis and contextual hermeneutics. The results show that the textual understanding of Milku Al-Yamīn in the Qur'an cannot be separated from the social and cultural context of the society when the verses were revealed. The Qur'an does not directly legalize slavery, but takes an evolutionary path by emphasizing liberation, justice, and respect for human dignity. In the modern context, scholars believe that Milku Al-Yamīn needs to be reinterpreted as a symbol of social transformation towards the elimination of oppression and inequality. Thus, through a reading that takes into account both the text and context, Milku Al-Yamīn is understood not as a legitimization of slavery, but as part of the moral and humanitarian process promoted by the Qur'an.